AMBATIG: Android Application for Generating Batik Motifs Using Frieze Symmetry Group Transformations - Dinda Kartika; Fevi Rahmawati Suwanto; Nurul Maulida Surbakti (UIN Sumatera Utara, 2025)
Indonesian batik is known for its diverse motifs, yet many artisans still design patterns manually, which limits variation and innovation. This study develops Ambatig, an Android application that helps artisans create batik motifs more efficiently. The application was implemented in Android Studio and follows a waterfall development model. Ambatig transforms a user drawn base cell into structured repetitions by composing distance preserving transformations, namely translation, vertical reflection, horizontal reflection, half turn rotation of 180 degrees, and glide reflection. These operations are configured according to the seven frieze types introduced in the study. Functional black box testing confirmed stable performance with all scenarios passing. Compared with previous motif generation approaches, Ambatig introduces a parameterized on device frieze transformation pipeline that produces all seven symmetry families from a single base motif. Real time preview and export features support creative exploration while maintaining mathematical coherence in digital batik design.